THE IMPACT OF COASTAL RECLAMATION ON THE EXISTENCE OF MACROZOOBENTHOS IN THE NAGARI MANDEH WATER AREA, PESISIR SELATAN DISTRICT, WEST SUMATRA - Ramadhan Ramadhan; Afrizal Tanjung; Elizal Elizal (Asian Journal of Aquatic Sciences, 2023)
This research aims to determine the description of the presence of macrozoobenthos which is thought to have been affected by coastal stockpiling which has recently been carried out around the Mandeh Tourism Area. This research was conducted in January - March 2022, the method used in this research is purposive sampling with sampling using the transect method. The results of this study indicate that the water quality of Nagari Mandeh is sufficient to support the life of macrozoobenthos, the macrozoobenthos found consist of 10 families, namely Arciidae, Cardiidae, Cerithiidae, Fasciolariidae, Neritidae, Potamididae, Psammobiidae, Tellinidae, Turbinidae, and Strombidae. The type of sediment in the waters of Nagari Mandeh consists of gravel sand, colloid, sandy silt, silty sand, and sandy gravel. The content of total organic matter (BOT) from sediments in the waters of Nagari Mandeh was found to be in the range of 8.08% - 15.25% (medium). Coastal reclamation activities do not have an impact on the presence and diversity of macrozoobenthos but have an impact on the types of individuals living around the reclamation area